The Role of Green Intellectual Capital in Promoting Cleaner Production Strategy - صادق كامل عبيد الحميري; محمود فهد عبد علي; علي عبد الحسن عباس (Iraqi Journal for Administrative Sciences, 2025)
The current study aimed to explore the impact of green intellectual capital on the cleaner production strategy. The study relied on the questionnaire as a primary tool for collecting data and information about the study community represented by a sample (275), which was represented by the workers in the Union Food Industries Company/Babil. The analysis and statistical processing were based on the SPSS and Amos programs (exploratory and confirmatory factor analysis, as basic structural tests for the validity of the adopted measures. The research relied on the descriptive analytical approach). Based on the study problem represented in knowing the strength of the influence between the research variables and their hypotheses, the researcher reached a set of conclusions, the most prominent of which was that the cleaner production strategy is a commitment by the business organization to environmental standards that lead to a gradual reduction in the amount of pollutants and avoiding penalties and fines imposed by governments due to pollution caused by the organization, in addition to improving the organization's relationship with the parties and organizations concerned with the environment and society. Green intellectual capital helps greatly in overcoming environmental crises, and the sustainable supply chain contributes to reducing energy and reducing industrial waste.